Strategi Pegembangan Usaha Beras Hitam pada Asosiasi Tani Organik Sawangan di Kabupaten Magelang - Stefani, Eska; Nurmalina, Rita; Rifin, Amzul (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2017)
The black rice farming is potential to be developed in Indonesia for several reasons, for instance it is a rare local varieties, has many health benefit, high value, and feaseable to be developed based on farming analysis. Magelang regency is a region that has original varieties of black rice. The development of black rice farming was supported by Association of Sawangan Organic Farmers. This study applied internal and external environment analysis and formulated strategy using SWOT analysis, and then the priority strategy was chosen by weighting it based on SWOT analysis framework (AâWOT). Result showed that certified organic product was the most important factor on strength while the decreasing number of black rice farmer was the weakness. Furthermore, increasing people awareness on healty food was the opportunity and the threat was black rice has not been widely known in public. The priority alternative strategy that can be applied by Association of Sawangan Organic Farmers to develop black rice farming is to build a sustainable business partner.